Daratumumab granted breakthrough drug status. (April 2014) - Laubach, Jacob P; Tai, Yu-Tzu; Richardson, Paul G; Anderson, Kenneth C
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) remains incurable despite important recent advances in treatment due to its inherent resistance, characterized by highly complex and heterogeneous molecular abnormalities, as well as the support from myeloma bone marrow (BM) microenvironment. A novel therapeutic strategy that effectively targets specific molecules on myeloma cells and also potentially overcomes tumor microenvironment-mediated drug resistance and the downstream effects of genetic instability is thus urgently needed. Over the last 2 years, an anti-CD38 monoclonal antibody daratumumab (DARA) has emerged as a breakthrough targeted therapy for patients with MM. Early-stage clinical trials have found DARA to be safe and to have encouraging clinical activity as a single agent and in combination with lenalidomide in heavily pretreated, relapsed patients in whom other novel agents (such as bortezomib, thalidomide and lenalidomide) as well as stem cell transplant has already failed. DARA may, therefore, be the first mAb with significant anti-MM activity both as a monotherapy and in combination. It is currently being further evaluated both alone and in combination with conventional and novel anti-MM agents as part of prospective clinical trials. This review discusses the preclinical and clinical development of DARA, its pathophysiological basis, and its prospects for future use in MM.